Modernitas Nusyuz; Antara Hak dan Kewajiban - Rizqa Febry Ayu; Rizki Pangestu (Program Studi Hukum Keluarga Islam, 2021)
Nusyuz is a wife's disobedience to her husband or to the rules that have been bound by an agreement that has been established because of the marriage bond without reasons justified by syara’. Allah determines the punishment for women who do nusyuz, which is found in QS. An-Nisa verse 34. Nusyuz does not only come from wives, husbands can also be said to be nusyuz if they do not fulfill their obligations in the household. This study focuses on the implications of nusyuz between rights and domestic violence. This research uses a qualitative study that is analytical descriptive method. The results showed that Islam obliges husbands to take three stages to cure the wife's nusyuz, first they have the right to give advice, second they have the right to separate from sleeping with them, the third have the right to beat them. The beatings must not hurt, this punishment is meant to be interpreted as an act to teach a lesson not to hurt. In addition, as the social conditions of society change, the concept of nusyuz needs to be reviewed, because for a wife who leaves the house without her husband's permission, it is considered as nusyuz not in accordance with the present context. In this research hitting is not a part of domestic violence but in the realm of rights but it is not recommended to hit until it causes violence. So in fact the existence of Law Number 23 of 2004 concerning Domestic Violence is to provide a safe presence of women from violence both from the public sphere and in the household.Nusyuz merupakan ketidakpatuhan istri terhadap suami ataupun aturan dan perjanjian yang telah ditetapkan sebelumnya melalui hubungan perkawinan tanpa sebab yang yang tidak disahkan oleh ajaran agama Islam. Allah menetapkan hukuman bagi wanita yang melakukan nusyuz yaitu terdapat dalam QS. An-Nisa ayat 34. Perilaku nusyuz tidak hanya dilakukan oleh istrin melainkan suami juga dapat dikatakan berbuat nusyuz jika suami tidak melakukan kewajibannya dengan baik sebagai suami. Penelitian ini bertujuan menjelaskan modernitas nusyuz antara hak dan KDRT. Penelitian ini menggunakan kajian kualitatif bersifat metode deskriptif analitis. Hasil penelitian menunjukkan bahwa Islam mewajibkan bagi para suami untuk menempuh tiga tingkatan untuk penyembuhan nusyuz istri, pertama berhak memberi nasihat, kedua berhak untuk berpisah tidur dengannya, ketiga berhak memukulnya. Pemukulan tersebut tidak boleh sampai melukai, hukuman ini hendak dimaksudkan untuk menyakiti melainkan untuk memberikan peringatan dan pelajaran bagi istrinya. Selain itu seiring perubahan kondisi sosial masyarakat, maka konsep nusyuz tersebut perlu ditinjau kembali, karena bagi istri yang keluar rumah tanpa seizin suami dianggap sebagai nusyuz tidak sesuai dengan konteks sekarang. Dalam penelitian ini memukul bukanlah termasuk KDRT melainkan dalam ranah hak akan tetapi tidak dianjurkan memukul sampai menimbulkan kekerasan. Maka sejatinya keberadaan UU No. 23 Tahun 2004 terkait KDRT dalam memberikan kenyamanan dan keamanan keberadaan perempuan dari kekerasan baik dari ruang publik maupun dalam rumah tangga.